Pediatric bladder/prostate rhabdomyosarcoma: Eight cases from a single center - Emir, Suna; Özdemir, Sonay İncesoy and Demir, Hacı Ahmet and Özyörük, Derya and Karakuş, Esra and Tiryaki, Tuğrul and Çetindağ, Faik (The Turkish Journal of Pediatrics, 2016)
In this study, clinical characteristics, treatment modalities and outcome of patients diagnosed with bladder/prostate rhabdomyosarcoma (BP RMS) were evaluated retrospectively. Files of 8 children diagnosed with BP RMS and treated between 2004-2014 were reviewed for clinical characteristics, treatment modalities and outcome. Seven males and one female were diagnosed with BP RMS between 2004-2014. Median age was 33.5 months (range, 2 to 176 months). At presentation the main clinical symptoms were hematuria in 5 patients, and constipation, oliguria and prolonged jaundice in 1 patient each. All patients were non-metastatic and only one had an embryonal histology. Primary resection before chemotherapy was performed on only one patient. Six patients were treated initially with VAC chemotherapy for 12 weeks, two patients were treated PIAV (ifosfamide, cisplatin, doxorubicin, vincristine). Local relapse or progressive disease occurred in 5 of 8 patients, and two of these patients underwent primary or secondary tumor resection without radiotherapy. Three patients developed a local relapse after combination of radiochemotherapy and tumor resection. Radical surgical treatment was performed in 3 patients with local relapse. Only one patient underwent partial cystectomy. Six of 8 patients were alive and under follow-up without disease at a median survival of 53 months (range, 13 to 78 months). BP RMS requires a multidisciplinary treatment approach. There is a general consensus that chemotherapy is the mainstay of treatment in BP RMS, but the method to be used for local control is controversial, and may vary from case to case in this heterogeneous disease.